Improving Fishermens Welfare with Fuel-Saving Technology - Darma, Surya; Darma, Dio Caisar; Hakim, Yundi Permadi; Pusriadi, Tommy (Journal of Asian Scientific Research, 2020)
The problem of energy for fishermen is indeed very complex. When fuel prices rise, it is very worrying that the poor in Indonesia will increase. The study aimed to find out the development of fishermen, as well as the benefits of using Brown’s Gas Electrolyzer (BG-E) on a fishing boat in Indonesia. This type of data is secondary and sourced from second parties (Government Office and others). Analysis, synthesis methods, and alternative problem solving are prepared based on data, information, and observations to solve fisherman's problems based on research objectives. The application of BG-E technology can be applied to small-scale fishing boats, is Outboard Motorboats and 5-30 GT Motorboats. BG-E is made according to the ship's power requirements. The way it works through an electrolysis process to decompose compounds in the form of solutions melts, or ordinary liquids by the electric current flowing through the compound. From the results of the electrolysis process, it produces oxyhydrogen which will react with gasoline in the boat engine. This reaction will produce an explosion to move the piston on the ship's engine so that the engine can live. With the implementation of BG-E, it can save fuel oil consumption and improve the welfare of Indonesian fishermen. The originality of the research is related to the method used in the framework of estimating Fishermen fuel savings in Indonesia, so that the study will become novelty in the future.